LEARNERS’ COMMENTS AS PEER FEEDBACK IN ENGLISH CONVERSATION CLASS - Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2017)
English lesson taught for undergraduate level is aimed at boosting their English proficiency as well as their performance. This study is conducted at FBIB Unisbank Semarang. The subjects of the study are the first semester students who took Performative Spoken English Class for the academic year of 2016/2017. This subject is aimed at improving students’ speaking skill especially in creating conversation using different speech events. Students belong to English Department should know how to use the right speech functions in their talks but due to their low level of speaking mastery therefore they have difficulty in using English properly. This study is conducted in order to help the new students to improve their English speaking skill so that they will be motivated in talking using English in their speaking class. Students as peer for their own classmates sometimes are not reluctant in giving comments though they realize that their peers need it. The teachers involve the students in giving their comments with the purpose to give positive feedback for their peers so that their English speaking skill will improve. Their comments are known as learners’ comments because they are English learners who take English class.The lecturers have the roles as the researchers therefore this study is called classroom reasearch. The researchers conducted research for one semester for the first semester students who belong to morning program. The number of students who are being observed is 20 students based on the list but in fact only 16 to 19 students who join the class. The researchers collected the data with the help of a student from regular morning program. The data are qualitative data in the form of learners’ comments in peer review rubric, teacher’s journals and teacher’s interpretation. After the students read the comments from their peer their motivation increased and their speaking skill slowly but surely improve.Keywords: Performative Spoken English, Learners’ comments, classroom research